2012
DOI: 10.1161/hypertensionaha.112.199919
|View full text |Cite
|
Sign up to set email alerts
|

A Mitochondrial Permeability Transition Pore Inhibitor Improves Renal Outcomes After Revascularization in Experimental Atherosclerotic Renal Artery Stenosis

Abstract: Revascularization improves blood pressure but not renal function in most patients with atherosclerotic renal artery stenosis (ARAS), possibly related to injury incurred during renal reperfusion. Bendavia, a novel tetrapeptide that inhibits mitochondrial permeability transition pore opening, reduces apoptosis, oxidative stress, and ischemia-reperfusion injury in experimental models. However, its potential for improving renal response to revascularization of chronic ARAS is unknown. We hypothesized that adjunct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
148
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 112 publications
(158 citation statements)
references
References 29 publications
9
148
0
Order By: Relevance
“…Similarly, Mizuguchi et al demonstrated that pretreatment of rats with Bendavia decreased renal damage and oxidative stress in a model of unilateral ureteral obstruction [19]. In line with these observations, we have recently shown in swine ARAS that systemic infusion of Bendavia during the PTRS procedure (from 30min before to 3.5 hours after PTRS), promoted renal mitochondrial biogenesis and attenuated microvascular remodeling, apoptosis, oxidative stress, tubular damage, and fibrosis evaluated four weeks after revascularization [20]. Furthermore, renal inflammation, one of the main determinants of disease progression and response to revascularization in ARAS [21], was restored to normal levels in Bendavia-treated pigs.…”
supporting
confidence: 85%
“…Similarly, Mizuguchi et al demonstrated that pretreatment of rats with Bendavia decreased renal damage and oxidative stress in a model of unilateral ureteral obstruction [19]. In line with these observations, we have recently shown in swine ARAS that systemic infusion of Bendavia during the PTRS procedure (from 30min before to 3.5 hours after PTRS), promoted renal mitochondrial biogenesis and attenuated microvascular remodeling, apoptosis, oxidative stress, tubular damage, and fibrosis evaluated four weeks after revascularization [20]. Furthermore, renal inflammation, one of the main determinants of disease progression and response to revascularization in ARAS [21], was restored to normal levels in Bendavia-treated pigs.…”
supporting
confidence: 85%
“…9,[40][41][42][43][44] Although it was known that SS-31 concentrates in the IMM and inhibits MPT, 10 its exact mechanism of action remained unclear. Because SS-31 carries a 3+ net charge, we hypothesized that it binds to the anionic phospholipid CL that is uniquely expressed on the IMM.…”
Section: Discussionmentioning
confidence: 99%
“…41 SS-31 can even improve kidney outcome after reperfusion after chronic ischemia in a porcine model of renal artery stenosis. 44 The validity of CL as a target for therapeutic development is currently being evaluated in a multinational clinical trial with Bendavia for reperfusion injury in patients with acute coronary events (NCT01572909), and a Phase 2 trial was just initiated to assess the effectiveness of Bendavia on improving renal function after angioplasty for severe renal artery stenosis (NCT01755858). …”
Section: Discussionmentioning
confidence: 99%
“…49 Intravenous administration of a mitochondrial-targeted peptide (SS31, Bendavia; Stealth Biopharmaceuticals, Boston, MA) during renal artery angioplasty in a swine model restored measures of mitochondrial biogenesis and limited vascular rarefication, apoptosis, oxidative stress, and fibrosis. 50 Remarkably, blood flow and GFR in the treated animals were restored to control levels, suggesting that sustained mitochondrial dysfunction may severely limit the potential benefits of restoring renal blood flow. Mitochondrial swelling and distortion are among the earliest histologic changes observed in temporary renal artery clamping in humans.…”
Section: Can Injury Within the Poststenotic Kidney Be Prevented Or Rementioning
confidence: 95%